Population‐based trends in prenatal screening and diagnosis for aneuploidy: a retrospective analysis of 38 years of state‐wide data. (25th June 2015) - Hui, L; Muggli, EE; Halliday, JL
Abstract : Objective: To analyse population‐based trends over the entire history of prenatal testing for aneuploidy. Design: Retrospective analysis of state‐wide data sets. Setting: Australian state of Victoria with 70 000 annual births. Population: All pregnant women undergoing invasive prenatal testing at <25 weeks' gestation from 1976 to 2013. Methods: Analysis of three state‐wide data sets: (1) Prenatal diagnosis data set of 119 404 amniocenteses and chorionic villus samplings from 1976 to 2013; (2) central serum screening laboratory data set from 1996 to 2013; (3) government birth statistics from 1976 to 2013. Main outcome measures: Annual numbers and uptake rates of invasive prenatal tests and serum screening, indications for invasive prenatal testing, prenatal diagnoses of aneuploidy, diagnostic yield of invasive tests. Results: Annual numbers of invasive prenatal tests climbed steadily from 1976, then declined from 2000. In 2013, the number of invasive prenatal tests was the lowest in 25 years, while the number of trisomy 21 diagnoses was the highest ever recorded. Annual uptake of serum screening climbed from 1.6 to 83% over 1996–2013. Results from 2013 showed a high diagnostic yield (15.8%) for a low rate of invasive testing (3.4% of births). Over four decades, the number of invasive procedures performed for each diagnosis of major chromosome abnormality declined from 100 to six. Conclusions: This study demonstrates historic reductions in the proportion of women undergoing invasive testing and dramatic improvements in diagnostic yield. Monitoring the impact of new prenatal technologies on this progress remains an important research priority. Tweetable abstract: Invasive prenatal testing has reached historic lows due to dramatic improvements in Down syndrome screening. Tweetable abstract: Invasive prenatal testing has reached historic lows due to dramatic improvements in Down syndrome screening.